(untitled) (International Journal of Occupational Safety and Health, 2012)
Mental health denotes a symptom free mind and fair level of emotional well being. Be it home or workplace; mental health of an individual is subjected to environmental stressors that may reduce one’s state of well being. The workplace in particular can be a very tiring environment for anyone. The stress of long working hours, ever increasing targets, managing coworkers and subordinates can take a toll on a persons mind and prove very toxic to one’s mental and physical health in long run. It is difficult for persons with full blown mental illness to continue at work; but it generally takes a gradual course, before an individual shows full blown symptoms of a particular illness. Thus it becomes necessary to constantly check mental health and stress level of workers. The article discusses mental health, particularly in work place occupational stress and the related issues. DOI: http://dx.doi.org/10.3126/ijosh.v2i1.5915 International Journal of Occupational Safety and Health, Vol. 2 No. 1 (2012) 2-6